Comparative Study of Thermal Criteria and Fluid-Flow Criteria in Micro and Mini Channel Design Constrains with or without Insert Made of Aluminum Material - Shivasheesh Kaushik; Jagdish Singh Mehta; Satyendra Singh; Vikas Singh Mahar; Ayushman Srivastav; Nikhil Kanoji; Raja Kumar; Samriddhi Vashisth; Shubham Singh Karki; Amit Kumar; Prabhakar Bhandari; Desh Bandhu Singh (International Journal of Integrated Engineering, 2024)
Through experimental and simulation results, a comparison between mini and micro channels with inserts or without inserts is conducted; in this case, water is the only working fluid used for present experimentation. In order to research the fluid flow and micro channel features, the results of fluid flowing inside the mini channel and micro channel with insert or without insert separately were admitted. Experiments were performed for various operating and design parameters under counter-flow conditions, with hot water moving into a concentric tube with a 30 mm diameter at 0.00078 kg/sec flow rate. The fluid is moving separately through mini channels with a 2 mm diameter and micro channels with lower than 1 mm dia. at a varying flow rate 0.00015 kg/sec to 0.0062 kg/sec. The working temperatures for hot water and cold fluid were 323 K and 303K, respectively. According to the results, the suggested design of the micro channel with insert performed better than a conventional mini channel, micro channel without insert and mini channel with inserts due to the better thermal conductivity of the aluminum material, effective diameter (1mm) to length ratio of micro channel in which heat exchanges with minimum volume ratio and the additional exposed area made possible by the rectangular shape of the insert, whereas micro channel with micro insert having rectangular shape showing best results as compared with the other designs of channel due to the rich heat passage and effective pressure drop and temperature. Experimentation and simulation results are coming in positive direction, it is directly observed from the error percentage i.e. 6%-8.2%.